Hydration of the DNA bases is local - Schneider, B; Berman, H M (Biophysical journal, 1995)
Ordered hydration sites were determined for the nucleotide bases in B-type conformations using the crystal structure data on 14 B-DNA decamer structures. A method of density representation was extended so that positions, occupancies, and distributions of the hydration sites were predicted around a B-DNA double helix by a method analogous to crystallographic refinement. The predicted hydration sites correctly reproduce the main features of hydration around the B-DNA dodecamer. In contrast to the previous observations, the newly available crystal data show the same extent of hydration of guanine and adenine, and of cytosine and thymine.
Keywords: Cytosine; sekvence nukleotidů; krystalografie rentgenová; Nucleic Acid Conformation; Guanine; Adenine; Databases, Factual; adenin; thymin; molekulární sekvence - údaje; databáze faktografické; vodíková vazba; Oligodeoxyribonucleotides; molekulární modely; Crystallography, X-Ray; Models, Molecular; oligodeoxyribonukleotidy; konformace nukleové kyseliny; cytosin; DNA; Molecular Sequence Data; Base Sequence; Thymine; Hydrogen Bonding; guanin